Hormonal Contraceptive Use in Football Codes in Australia - Clarke, Anthea C.; Bruinvels, Georgie; Julian, Ross; Inge, Pip; Pedlar, Charles R.; Govus, Andrew D. (Frontiers in Sports and Active Living, 2021)
The recent launch of the new National elite women's football competitions in Australia has seen a 20–50% increase in grassroots female participation. With the growing participation across grassroots to elite competitions, understanding the health of female athletes should be prioritized. In elite level athletes, hormonal contraceptive (HC) use is common ( 50%), however, little is known about the prevalence and reasons for use and disuse of HC in elite female football athletes. As such, the impact of HC use is often not considered when monitoring the health of female footballers. This study involved a subset of data collected as part of a larger questionnaire investigating menstrual cycle function, hormonal contraception use, and the interaction with training load volume and perceived performance in elite female football code athletes. A total of 177 participants completed the questionnaire across three football codes within Australia (rugby league, rugby union/sevens, Australian football). One third (n = 58) of athletes were currently using HC, predominately in the form of an oral contraceptive pill (OC, n = 47). Reasons for use included: to avoid pregnancy (71%); to control/regulate cycle (38%); and to reduce menstrual pain (36%). However, most athletes using an OC (89%) could not identify the type of pill used (e.g., mono-, bi-, or triphasic). The main reason for disuse was due to the negative side effects (n = 23), such as mood swings, weight gain, and depression/anxiety. Comparing HC users and non-users, there were no statistical differences in the number of reported menstrual symptoms, use of medication to relieve menstrual pain, or frequency for needing to adapt training due to their menstrual cycle (p > 0.05). Since most athletes were unaware of the type of OC they used, female football athletes require further education about the different types of HC, and specifically OC, available to them. Similarities in the symptoms experienced, pain management, and training adaptation requirements between groups suggests that HC use may not have the intended outcome for certain athletes. As such, greater awareness of athlete's personal experiences with the menstrual cycle, how HC may influence their experience, and acknowledgment of non-pharmacological methods to help manage menstrual cycle related symptoms are warranted.